Reopening the criminal prosecution to ensure an effective investigation - Lorincz, Anca-Lelia (International Journal of Legal and Social Order, 2023)
The respect of the fundamental rights of the person during the criminal judicial proceedings is also conditional on the performance of an effective investigation. Although, in the current Romanian Code of Criminal Procedure, the principle of the active role of judicial bodies in the conduct of the criminal process is no longer expressly provided for, the need to manifest such an active role, in the sense of carrying out a real, complete, therefore effective criminal investigation, emerges from the content of the provisions art. 5 ("Finding the truth") and art. 306 ("Obligations of criminal prosecution bodies"). The requirement of the effectiveness of the criminal investigation is also reflected in the jurisprudence of the European Court of Human Rights (even if, for now, mainly in relation to articles 2 and 3 of the European Convention for the Protection of Human Rights and Fundamental Freedoms). In this context, the present study addresses the issue of resuming the criminal prosecution by reopening it, in the situation where the case closure solution was ordered without conducting an effective criminal investigation. The paper also brings to attention some aspects of judicial practice regarding the confirmation, by the judge of the preliminary chamber, of the ordinance to reopen the criminal prosecution. The study uses, as research methods: documentation, interpretation and scientific analysis.